(untitled) (Ciencias de la Ingeniería y Aplicadas, 2021)
In Electrical Power Systems (SEP), it is very important to guarantee the continuity of the electrical service in the presence of electrical failures, as well as safeguard the integrity of the equipment that makes up a SEP. To achieve this objective, different equipment is used such as: inverse and definite time overcurrent relay. The present project focused on the construction of a prototype of a defined inverse time overcurrent relay, using mathematical models defined in the IEC 2554 and BS142 Standard, the module contains a human machine interface (HMI), which facilitates the reading of current such as operation times and the entry of variables such as Dial, TAP and curve type selection, essential parameters for calibration. The current signal is measured by a hall effect sensor, which is connected to an analog input of the Arduino card, the signal is processed so that an effective value (RMS) is obtained, representing the value measured in the secondary of a current transformer TC, consequently the prototype calculates the operation time at different Dial and Tap configurations, where the module allows a minimum response time of 9 milliseconds when it reaches the defined time configuration. Keywords: Inverse and definite time overcurrent, electrical protections, continuity of electrical service.